Jumlah Bakteri pada Udara Ruang Tunggu Puskemas - fahrul islam; haeranah ahmad; askur (Jurnal Kesehatan Komunitas, 2022)
Air quality in the public health center waiting room as one of the facilities of public places is influenced by several factors including; room condition, humidity, temperature, lighting, and microbiological content. Nosocomial infectious diseases are often sourced from health facilities where healthy people can become sick and sick people can gain additional burden from the spread of pathogenic microbes in the air. The purpose of this study is to find out the amount of airborne bacteria in the waiting room of puskesmas in Mamuju subdistrict. This study is an observational study with a descriptive approach through measurement and laboratory examination. The air bacteriological sampling method uses the volumetric air sampling method. The tool used in the capture of airborne bacteria in this study was Microbio MB2. The tool used to measure temperature and humidity is Humidity Alert II Extech 445815 and the tool for measuring lighting is Digital Light Meter TASI-8720 Sampling is done in the morning for 3 (three) days in a row. The results of the study: The average temperature in the waiting room of the public health center of Binanga is 29.80C, while the public health center of Bambu is 28.90C. The average humidity in the waiting room of the public health center of Bambu is 70.3% while the public health center of Binanga 65%.. The average lighting in the waiting eoom of public health center of Binanga is 215.9 lux and the public health center of Bambu is 139.5 lux. The total number of germs in the waiting room of the public health center of Bambu is on average 258 CFU / m3 while the public health center of Binanga is 513 CFU / m3. Conclusion: the number of bacteria in the waiting room of public health center of Binanga is more than Bambu. Suggestion: health workers and the community to use personal protective equipment (masks) if they are around the public health center